Hubungan Perilaku Pedagang Terhadap Kandungan Formalin Pada Ikan Teri Asin (Stolephorus Sp) di Pasar Tradisional Kota Magelang - Putri, Meisilvi Rezeki Isa; Santoso, Lutfi; Martini, Martini (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Salted fish is one type of food that is easily available in the market, either traditional and modern market. Formalin is widely used as a food preservative. Formalin can be harmful to health if consumed. The purpose of this study is to analyze the correlation between behavior of sellers with formaline content in salted fish sold in the traditional market town of Magelang city. This research is explanatory research, using survey methods with cross sectional approach. The population in this study is the seller salted fish who are in the traditional market Magelang city. There are four markets and the sellers are 34 people. The sample of this research is 34 sellers. The results showed that 30 of 34 samples of salted fish were tested in the laboratory were qualitatively positive for formaline. As for the formaline test on the quantitative, the average of formaline content in salted fish is 1564.422 ppm. The conclutions are behavioral factors obtained from sellers there is a relationship between seller knowledge about formaline with formaline content in salted fish (p = 0.031), there is a relationship between seller attitudes toward formaline with formaline content in salted fish (p = 0.006) and there was no relationship between the seller practice to give formaline with formaline content on the salted fish (p = 0.678). The need for supervision and counseling of related agencies. Traders should keep a salted fish in the freezer. For communities to be more padai in choosing salted anchovies and need to add knowledge about safe food for consumtion.